An Overview of Gastroduodenal Perforation - Weledji, Elroy Patrick (Frontiers in Surgery, 2020)
Gastric perforations may be spontaneous or traumatic and the majority of spontaneous perforation is due to peptic ulcer disease. Improved medical management of peptic ulceration has reduced the incidence of perforation, but still remains a common cause of peritonitis. Sub-diaphragmatic air on chest x-ray may be absent and computed tomography scan is a more sensitive investigation in the stable patient. The management of perforated peptic ulcer disease is still a subject of debate The majority of perforated peptic ulcers are caused by Helicobacter pylori, so definitive surgery is not usually required. Perforated peptic ulcer is an indication for operation in nearly all cases except when patient is unfit for surgery. Non-operative management has a high incidence of intra-abdominal abscesses and sepsis. Primary closure is achievable in traumatic perforation, but the management follows the Advanced Trauma Life Support (ATLS) principles.